Benin: Recent developments in agricultural research - Stads, Gert-Jan; Hinvi, Jonas (International Food Policy Research Institute, 2010)
Since the turn of the millennium, total investments in agricultural research and development (R&D) in Benin have been on the increase. In 2008, the country's expenditures totaled approximately 4.7 billion CFA francs or 21.6 million PPP dollars (both in constant 2005 prices). Unless otherwise stated, all dollar values in this note are based on purchasing power parity (PPP) exchange rates. PPPs reflect the purchasing power of currencies more effectively than do standard exchange rates because they compare the prices of a broader range of local—as opposed to internationally traded—goods and services. Total agricultural R&D capacity levels in Benin reveal a negative trend. In 2008, the country employed 115 full-time equivalent (FTE) research staff, compared with 120 FTEs in 2000. This attrition mainly resulted from staff retirement at National Agricultural Research Institute of Benin (INRAB) in combination with a publicsector recruitment freeze that has been in place since the 1980s.